2022
DOI: 10.15561/26649837.2022.0602
|View full text |Cite
|
Sign up to set email alerts
|

Housework-based exercise versus conventional exercise on health-related fitness of adolescent learners

Abstract: Background and Study Aim. There is a void in the literature comparing the fitness effects of housework-based exercise (HBE) and conventional exercise (CE), including studies that adapt housework into an exercise program. This study examines the effectiveness of HBE and CE on adolescent learners' health-related fitness (HRF) and compares the effectiveness of the two exercises. Material and Methods. This study uses a parallel-group, randomized controlled trial with 120 adolescent learners; 60 are in the HB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…A study of adolescents randomized the adolescents between conventional exercise and housework-based exercise. Housework was concluded to be just as good for keeping or improving adolescent learners' fitness [32]. Hence, our findings from NHPI and Asian survey respondents are in line with other studies that have found the important contribution of household activities to moderate-to-vigorous activity.…”
Section: Discussionsupporting
confidence: 90%
“…A study of adolescents randomized the adolescents between conventional exercise and housework-based exercise. Housework was concluded to be just as good for keeping or improving adolescent learners' fitness [32]. Hence, our findings from NHPI and Asian survey respondents are in line with other studies that have found the important contribution of household activities to moderate-to-vigorous activity.…”
Section: Discussionsupporting
confidence: 90%
“…For PE teachers, transitioning from in-person movement-oriented content to online presents a monumental challenge , especially knowing that PE has been deliberately taught face-to-face. Moreover, the expectation of developing learning opportunities that support students' attainment of curriculum standards and grade-level outcomes comparable to those implemented in face-to-face contexts is challenging for PE teachers (Harris & Metzler, 2019;Tanucan et al, 2022a). This situation could be worsened when necessary training is absent.…”
Section: Discussionmentioning
confidence: 99%
“…The shift to MDL has proven difficult and frustrating for many students (Ariza & Ariza, 2021;Meniano & Tan, 2022). Many were confused, stressed, and unsure of their learning from a distance (Espina & Monte, 2022;Geroso & Aloba, 2021, Tanucan et al, 2022b, which was often caused by less support from parents and teachers, along with other external factors like poor learning environment (Aksan, 2021;Butial et al, 2022). This situation has led to poor learning outcomes (Ariza & Ariza, 2021) and could impact the socio-emotional regulation of students due to prolonged independent learning.…”
Section: Theme 3: Intervention Presencementioning
confidence: 99%